Korupsi dan Pertumbuhan Ekonomi Daerah: Kajian Literatur - Akbar, Muhammad Rizky; Putri, Dea Pratama; Sapitri, Nor (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The impact of corruption on regional economic growth in Indonesia is discussed in this article through literature analysis. Corruption is considered a major obstacle to development because it can hamper budgets, stop investment, and undermine public trust in the government. Previous studies have shown that the relationship between corruption and economic growth is very complex, depending on how good the institutions and governance are in the region. To analyze these dynamics, this article uses a literature review technique from various national and international journals, as well as official institutional reports. The study shows that corruption in the region can reduce GRDP, infrastructure quality, and investor participation. However, corruption can function as a “lubricant” that accelerates economic processes in certain situations in countries with very slow bureaucracies, although its long-term consequences remain detrimental. Consequently, to suppress corruption and promote sustainable economic growth, comprehensive institutional reform, increased transparency, and public oversight are needed.